The Correlation Between Students’ Motivation to Study and Their Individual Listening to English - Azzeddine, BOULFELFEL (Journal of Human Sciences, 2009)
This paper investigates listening comprehension and motivation. It is composed of a theoretical aspect and a practical one. In the theoretical aspect, it first defines listening, putting a special emphasis on its nature as well as the problems encountered by L2 learners, notably individual L2 listeners in English. Motivation is then introduced and defined. It will be shown how motivation represents a key element in learning and achievement. At last, intrinsic motivation and extrinsic motivation are compared, focusing particularly on the main differences between them. In the practical aspect, the link between listening and motivation is investigated by means of two questions in the questionnaire. It has been shown that extrinsically motivated students, who represent a majority, do not actually listen regularly to English outside their classes- an intrinsically motivated behaviour. Thus listening and motivation have proved that they could be paired up together